Leakage Fault Diagnosis of Lifting and Lowering Hydraulic System of Wing-Assisted Ships Based on WPT-SVM - Ranqi Ma; Haoyang Zhao; Kai Wang; Rui Zhang; Yu Hua; Baoshen Jiang; Feng Tian; Zhang Ruan; Hao Wang; Lianzhong Huang (Journal of Marine Science and Engineering, 2022)
Wing-assisted technology is an effective way to reduce emissions and promote the decarbonization of the shipping industry. The lifting and lowering of wing-sail is usually driven by hydraulic system. Leakage, as an important failure form, directly affects the safety as well as the functioning of hydraulic system. To increase the system reliability and improve the wing-assisted effect, it is essential to conduct leakage fault diagnosis of lifting and lowering hydraulic system. In this paper, an AMESim simulation model of lifting and lowering hydraulic system of a Very Large Crude Carrier (VLCC) is established to analyze the operation characteristics of the hydraulic system. The effectiveness of the model is verified by the operation data of the actual hydraulic system. On this basis, a wavelet packet transform (WPT)-based sensitive feature extracting method of leakage fault for the hydraulic system is proposed. Subsequently, a support vector machine (SVM)-based multi-classification model and diagnosis method of leakage fault are proposed. The study results show that the proposed method has an accuracy of as high as 97.5% for six leakage fault modes. It is of great significance for ensuring the reliability of the wing-sail operation and improving the utilization rate of the offshore wind resources.

A new method for retrieving urban heat island intensity using GNSS-derived ZTD and atmospheric empirical model - Qimin He; Li Li; Dajun Lian; Hang Yu; Guodong Chen; Biqing Gao; Rui Wang; Kangming Song; Long Li (International Journal of Remote Sensing, 2022)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Emission reduction cooperation in a dynamic supply chain with competitive retailers - Jun Wang; Rui Ma; Xinman Lu; Baoqin Yu (Environment, Development and Sustainability, 2022)

Baicalin-berberine complex nanocrystals orally promote the co-absorption of two components - Ziwei Li; Yiting Liu; Jilin Wang; Xiaojiao Feng; Ebuka-Olisaemeka Nwafor; Ying Zhang; Rui Liu; Wenli Dang; Qingqing Zhang; Changxiang Yu; Jiaxin Pi; Zhidong Liu (Drug Delivery and Translational Research, 2022)

Effects of STAT3 Inhibitor BP-1-102 on The Proliferation, Invasiveness, Apoptosis and Neurosphere Formation of Glioma Cells in Vitro - Cheng-Chen Zhang; Ting Wu; Li Guan; Yu-Jue Wang; Rui-Qin Yao; Dian-Shuai Gao; Feng Li (Cell Biochemistry and Biophysics, 2022)

Analysis of Cyclic Shear Stress–Displacement Mechanical Properties of Silt–Steel Interface in the Yellow River Delta - Peng Yu; Jie Dong; Haisong Liu; Rui Xu; Rujie Wang; Meijun Xu; Hongjun Liu (Journal of Marine Science and Engineering, 2022)
Pile foundations of offshore structures are often subjected to cyclic loads under storm loads, thus reducing their vertical bearing capacity. Therefore, studying the cyclic shear behavior of the soil–structure interface is important for maintaining the stability of offshore structures. A series of cyclic shear tests of the silt–steel interface were carried out using a large interface shear apparatus. The effects of various factors (i.e., normal stress, shear displacement amplitude, roughness, and water content) on the shear stress characteristics of the silt–steel interface were investigated. The stress–displacement model of the cyclic shear silt–steel interface was deduced. The results showed that the shear stress at the silt–steel interface was softened, and the type of bulk deformation was shear shrinkage under cyclic shear. With the increase in shear amplitude, the hysteresis curve gradually developed from “parallelogram” to “shuttle” and “hysteresis cake”. With the increase in normal stress and roughness and the decrease in water content, the interfacial shear strength, volume displacements growth rate, and growth rate increased. The stress–displacement mathematical model of the silt–steel interface based on the modified hyperbolic model was in good agreement with the test data.

Counter-toppling force on the composite pile with injected grout for a precast spur dike - Minxi Zhang; Yikang Liao; Meixin Yu; Rui Wang; Guoliang Yu (Marine Georesources & Geotechnology, 2022)

Tectonic framework of Eastern Tianshan in the Early Carboniferous: constraints from alkalic intrusive rocks - Yi-Hao Liu; Chun-Ji Xue; Yun Zhao; Rui Wang; Liang Yu (International Journal of Earth Sciences, 2022)

Accelerated carbonate dissolution caused by anthropogenic acidification — contrast of watershed soils to lake sediments in Taihu Region, China - Yu Tao; Jia Binyang; Wang Rui; Deng Yixiang; Zhuo Xiaoke; Cheng Zhonghua; He Chengda (Environmental Science and Pollution Research, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

SLAH1 is involved in the long-distance transport of Cl− from roots into shoots in the Cl−-tolerant xerophyte Pugionium cornutum under salt stress - Yan-Nong Cui; Xiao-Yu Li; Rui-Wen Liu; Zi-Hua He; Suo-Min Wang; Qing Ma (Plant and Soil, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Integration of ABC curve, three dimensions of alpha diversity indices, and spatial patterns of fish assemblages into the health assessment of the Chishui River basin, China - Fandong Yu; Fei Liu; Zhijun Xia; Chunsen Xu; Jianwei Wang; Rui Tang; Zujun Ai; Youzhao Zhang; Miaomiao Hou; Xinhua Zou (Environmental Science and Pollution Research, 2022)

The protective effects of procyanidin supplementation on PM2.5-induced acute cardiac injury in rats - Bowen Yin; Xiao Zhang; Jingyi Ren; Fengge Chen; Jufeng Liang; Hanning Zhang; Huanting Pei; Zhaohui Hu; Yan Wang; Wei Xue; Xinyue Yu; Rui Zhang; et al. (Environmental Science and Pollution Research, 2022)

Maternal obesity induces liver lipid accumulation of offspring through the lncRNA Lockd/mTOR autophagy pathway - Rui Chen; Hongguang Yang; Yong Song; Hongjie Yu; Minzhe Zhang; Weiming Rao; Yaxu Wang; Xiaoyue Xiao; Qiutong Chen; Qiqiang He (Molecular Genetics and Genomics, 2022)

Spatiotemporal Variations of Microwave Land Surface Emissivity (MLSE) over China Derived from Four-Year Recalibrated Fengyun 3B MWRI Data - Rui Li; Jiheng Hu; Shengli Wu; Peng Zhang; Husi Letu; Yu Wang; Xuewen Wang; Yuyun Fu; Renjun Zhou; Ling Sun (Advances in Atmospheric Sciences, 2022)

Strength and microstructural characteristics of cement-solidified salt-rich dredged silt modified by nanoparticles - Shiquan Wang; Lei Lang; MingLi Wei; Xingxing He; Rui Wang; Chen Yu; Songbao Feng; Zhiyong Niu; Hongrui Ma (Marine Georesources & Geotechnology, 2022)

Research on PEMS Test Data Processing Method and Cold Start Emission Evaluation Method of Heavy-Duty Diesel Vehicles - Gangzhi Tang; Shuaibin Wang; Rui Wang; Baocheng Du; Yu Liu; Gang Tian; Linyao Ran; Gan Xiang; Huang Li (Water, Air, & Soil Pollution, 2022)

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

Proteomic analysis of coarse and fine skin tissues of Liaoning cashmere goat - Zhixian Bai; Yanan Xu; Ming Gu; Weidong Cai; Yu Zhang; Yuting Qin; Rui Chen; Yinggang Sun; Yanzhi Wu; Zeying Wang (Functional & Integrative Genomics, 2022)

Hierarchical collagen fibers complexed with tannic acid and Fe3+ as a heterogeneous catalyst for enhancing sulfate radical-based advanced oxidation process - Rui Wang; Ruiquan Yu; Junchao Wang; Jun Xiang; Chaojian Chen; Gongyan Liu; Xuepin Liao (Environmental Science and Pollution Research, 2022)

The effects of dietary fermented wheat bran polysaccharides on mucosal and serum immune parameters, hepatopancreas antioxidant indicators, and immune-related gene expression of common carp (Cyprinus carpio) juveniles - Rui-Fang Wang; Yuan Wang; Jun Zhang; Mei-Qi Weng; Yu-Hui Liu; Qiu-Yan Cheng; Min Song; Yan-Ping Yang; Xiao-Ping An; Jing-Wei Qi (Aquaculture International, 2022)

Mesoscale eddies induce variability in the sea surface temperature gradient in the Kuroshio Extension - Rui Tang; Yi Yu; Jingyuan Xi; Wentao Ma; Yuntao Wang (Frontiers in Marine Science, 2022)
The Kuroshio Extension (KE) region is one of the most energetic regions in the global ocean where prominent mesoscale dynamics persistently occur. The spatial distribution and temporal evolution of the sea surface temperature (SST) gradient and mesoscale eddies in the KE are investigated. The SST gradient can be applied for identifying the fronts, and the SST gradient within two times the radii of the eddies is composited to quantify the impact of eddies on frontal activities. Depressed SST gradients are identified for eddies with both polarities, but prominent spatial variance in the SST gradient reveals that a large SST gradient is located to the north of anticyclones and along the south periphery for cyclones. The eddies are further separated into two groups depending on their location relative to the main path of the KE, as the background fields to the north and south of the KE are largely different. The spatial pattern, e.g., monopole and dipole features, and temporal variation in the SST gradient are fully studied over the lifespans of eddies. The results show that most eddies can significantly weaken the internal SST gradient and induce the horizontal redistribution of the SST gradient in surrounding regions. Cyclonic eddies north of the KE elevate the fronts along the periphery of eddies. The temporal variability in the SST gradient is prominent and largely varies for each group of eddies. This study offers quantitative analyses of the spatial and temporal relationships between eddies and fronts that are important for understanding the mesoscale dynamics in the world’s oceans.

Hydrochemical Evolution and Nitrogen Behaviors in Coastal Groundwater Suffered From Seawater Intrusion and Anthropogenic Inputs - Yu Dun; Junhong Ling; Rui Wang; Jun Wei; Qianyi Zhou; Yingjie Cao; Yizhang Zhang; Yingxue Xuan (Frontiers in Marine Science, 2022)
Coastal aquifers play key roles in providing freshwater resources to maintain the social and economic development in coastal areas. However, climate change and human activities have dramatically affected the quantities and qualities of groundwater in coastal aquifers. In this study, stoichiometric analysis of hydrogeochemistry, multivariate analysis, and isotopic trancing techniques were used to reveal the local hydrochemistry characteristics, the natural and anthropogenic origins, and the major hydrochemical evolution in a typical coastal aquifer located in the Pearl River estuary. According to hydrogeological conditions and groundwater burial conditions, the aquifer was divided into three zones, namely, semiconfined fissure groundwater (SFGW), recharged fissure groundwater (RFGW), and porous medium groundwater (PGW). Seawater intrusion, ion exchange, water–rock reaction, and human activities were the main controlling factors affecting the characteristics of groundwater, but there were significant differences in the main controlling effects of different zones. Among them, the samples from the SFGW was severely affected by seawater intrusion, and the contributions of seawater ranged from 6% to 97%. Obvious cation exchange process occurred during the seawater intrusion. The hydrochemical characteristics of the PGW and the RFGW were mainly controlled by water–rock interaction. In addition, human activities had further influence on the hydrochemical characteristics of groundwater, which resulted in elevated nitrate–nitrogen (NO 3 − –N). The mean NO 3 –N concentrations in the PGW and the SFGW were 6.58 and 3.07 mg/L, respectively. Furthermore, the δ 15 N–NO 3 − and δ 18 O–NO 3 − values in these two regions ranged from +2.35‰ to +27.54‰ and from +0.39‰ to +18.95‰, respectively, indicating that the anthropogenic input contributed to the increased nitrate. Redox analysis and dual nitrogen isotopic evidence indicated that denitrification was the predominant biogeochemical process in the PGW and the RFGW. This study highlights the impacts of seawater intrusion and anthropogenic inputs on hydrochemical evolution and nitrogen behaviors in coastal groundwater, which provides a scientific basis for the management of groundwater resources in coastal aquifers.

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

IDDLncLoc: Subcellular Localization of LncRNAs Based on a Framework for Imbalanced Data Distributions - Yan Wang; Xiaopeng Zhu; Lili Yang; Xuemei Hu; Kai He; Cuinan Yu; Shaoqing Jiao; Jiali Chen; Rui Guo; Sen Yang (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Application of nanostructures as antimicrobials in the control of foodborne pathogen - Yu Tian; Rui Cai; Tianli Yue; Zhenpeng Gao; Yahong Yuan; Zhouli Wang (Critical Reviews in Food Science and Nutrition, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Identification and Expression Analysis of the SBP-box Gene Family Related to Abiotic Stress in Tea Plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Hao Liu; Yu Wang; Jing Zhuang (Plant Molecular Biology Reporter, 2022)

Study on mechanical properties and damage mechanism of strongly weathered gneiss under freeze–thaw cycles - Xianghui Deng; Yu Zhang; Rui Wang; Dongyang Yuan (Arabian Journal of Geosciences, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

A Reliable Murine Model of Disseminated Infection Induced by Talaromyces Marneffei - Juan He; Jia-Sheng Li; Hong-Yan Xu; Yi-Qun Kuang; Jun Li; Hong-Bin Li; Zhe Li; Hui-Ling Zhou; Rui-Rui Wang; Yu-Ye Li (Mycopathologia, 2022)

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

Four new indole alkaloids from the roots of Isatis tinctoria - Dongdong Zhang; Yu Sun; Yanhong Shi; Ximin Wu; Qi Jia; Kaixian Chen; Yiming Li; Rui Wang (Natural Product Research, 2022)

Enhanced stripe rust resistance obtained by combining Yr30 with a widely dispersed, consistent QTL on chromosome arm 4BL - Shengjie Liu; Xiaoting Wang; Yayun Zhang; Yangang Jin; Zhonghua Xia; Mingjie Xiang; Shuo Huang; Linyi Qiao; Weijun Zheng; Qingdong Zeng; Qilin Wang; Rui Yu; et al. (Theoretical and Applied Genetics, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Serine protease HtrA2/Omi regulates adaptive mitochondrial reprogramming in the brain cortex after ischemia/reperfusion injury via UCP2-SIRT3-PGC1 axis - Hao Meng; Lian-Kun Sun; Jing Su; Wan-Yu Yan; Yao Jin; Xin Luo; Xian-Rui Jiang; Hong-Lei Wang (Human Cell, 2022)

Laser ablation inductively coupled plasma mass spectrometry analysis of Chinese lead-barium glass: combining multivariate kernel density estimation and maximum mean discrepancy to reinterpret the raw glass used for producing lead-barium glass - Qian Ma; Rui Wen; Yifan Yu; Long Wang; Man Li; Luwu Cai; Li Ping; Zhiqiang Zhao; Dong Wang; Xiang Wang; Ruoyu Shi; A. Mark Pollard (Archaeological and Anthropological Sciences, 2022)

A Strategy for the Effective Optimization of Pharmaceutical Formulations Based on Parameter-Optimized Support Vector Machine Model - Siqi Wang; Jianping Yang; Hengwei Chen; Kexin Chu; Xuefei Yu; Yaqiong Wei; Haixia Zhang; Mengjie Rui; Chunlai Feng (AAPS PharmSciTech, 2022)